2006
DOI: 10.1016/j.jacc.2006.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Rest and Reserve Function in Patients With Fontan Circulation

Abstract: Because normal ventricular-vascular interaction and augmentation of cardiac performance during increased HR and adrenergic stimulation are important for maintaining cardiac output and exercise capacity, the present results may have important implications for the mechanisms underlying adverse outcome after Fontan surgery. Thus, improvement of long-term prognosis of patients after Fontan surgery requires the development of medical interventions that can overcome such limitations inherent in Fontan circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
104
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 152 publications
(110 citation statements)
references
References 40 publications
(45 reference statements)
5
104
0
Order By: Relevance
“…There was no difference in BNP between male and female patients (14 [IQR 6-33] vs. 13 [IQR 7-25] pg/ml), nor between patients with left or right ventricular morphology (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) vs. 14 [IQR 7-41] pg/ml).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no difference in BNP between male and female patients (14 [IQR 6-33] vs. 13 [IQR 7-25] pg/ml), nor between patients with left or right ventricular morphology (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) vs. 14 [IQR 7-41] pg/ml).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, one possible explanation for the surprisingly low BNP levels is the reduced ventricular preload in patients with Fontan circulation together with a limited preload reserve [15,16].…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, Fontan patients often have suboptimal hemodynamic conditions compared with normal biventricular subjects, such as higher venous pressure and lower CO (58,59). More importantly, the single-ventricle defect significantly impairs the regulatory capacity of the circulatory system, resulting in profound cardiovascular limitations under stress, typically during exercise (27,62,76).…”
mentioning
confidence: 99%
“…A study by Szabo et al (40) reported increased E a and decreased E es as well using pressure-volume analysis conducted on measurements made in a dog SV model. In addition to experimental studies, theoretical models have also predicted similar changes in E a , E es , and cardiac reserve in a Fontan circulation (14,22,28).Most of the studies thus far on the Fontan circulation can be broadly categorized into two types: 1) those that study the Fontan circulation as a whole using in vivo animal and human studies (35,36,40); and 2) those that study the fluid mechanics of the surgically created TCPC in isolation from the SV circulation (27,41,42). There have not been many studies that have connected the two, i.e., those that relate the hemodynamics of the TCPC to upstream hemodynamics and cardiac function.…”
mentioning
confidence: 99%
“…Most of the studies thus far on the Fontan circulation can be broadly categorized into two types: 1) those that study the Fontan circulation as a whole using in vivo animal and human studies (35,36,40); and 2) those that study the fluid mechanics of the surgically created TCPC in isolation from the SV circulation (27,41,42). There have not been many studies that have connected the two, i.e., those that relate the hemodynamics of the TCPC to upstream hemodynamics and cardiac function.…”
mentioning
confidence: 99%